(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
The research aims to analyze the factors influencing consumer demand after 2003, to know the relative importance of each group of commodity totals in per capita consumption spending after 2003, and to measure the impact of the factors influencing the consumption function after 2003, assuming the existence of a set of economic variables, internal and external, Which had an impact on household consumption spending in Iraq after 2003. The study concluded that an increase in oil prices by one unit increases household consumption spending by 0.04, and that an increase in population size by one unit increases household consumption spending by 0.2, and the impact of the Corona pandemic has a negative impact on household consumption spending, as it reduced it by 1.1 percent of spending. consumption on essential commodities, due to the tendency of household consumption to other commodities such as treatment, and an increase in the average per capita share by one unit leads to an increase in household consumption expenditure by 0.06